Institutionalizing Workplace Ethics And Values: Obligation For Organizational Success - Dr. Aneesya Panicker (International Journal of Advanced Science and Technology, 2020)
A successful organisation is one which believes in enforcing a clearly written, functional and obligatory code of ethics at its workplace for benefiting its management, employees and the general public. When organisations and its staff think of the significance of workplace ethics, they normally think about safety against dishonest behavior and unlawful conduct on the job. Workplace ethics focus on the protection of basic human rights in the organisations. It means it believes that employees should not be discriminated on the grounds of race, gender and disability, which leads to dissatisfaction, frustration, demotivation and anger among employees and ultimately gives the birth to the big organisational troubles like high absenteeism, increased grievances and attrition rate. An effective leader and manager should genuinely care their employees and should try to protect the fundamental right of its staff. They should promote the intensity of workplace values and ethics to spread happiness and high degree of belongingness among their employees which ultimately benefits workplace productivity and organisational public image. This paper is a conceptual paper based on the literature related to ethics and values at the workplace, their significance and application, leaders’ role in developing workplace ethics and various strategies to develop and strengthen the ethical behavior at the workplace.